Assessment of Detoxification Efficacy of Irradiation on Zearalenone Mycotoxin in Various Fruit Juices by Response Surface Methodology and Elucidation of Its in-vitro Toxicity - Kalagatur, Naveen Kumar; Kamasani, Jalarama Reddy; Mudili, Venkataramana (Frontiers in Microbiology, 2018)
Fruits are vital portion of healthy diet owed to rich source of vitamins, minerals, and dietary fibers, which are highly favorable in keeping individual fit. Unfortunately, these days, one-third of fruits were infested with fungi and their toxic metabolites called mycotoxins, which is most annoying and pose significant health risk. Therefore, there is a need to suggest appropriate mitigation strategies to overcome the mycotoxins contamination in fruits. In the present study, detoxification efficiency of irradiation on zearalenone (ZEA) mycotoxin was investigated in distilled water and fruit juices (orange, pineapple, and tomato) applying statistical program response surface methodology (RSM). The independent factors were distinct doses of irradiation and ZEA, and response factor was a percentage of ZEA reduction in content. A central composite design (CCD) consists of 13 experiments were planned applying software program Design expert with distinct doses of irradiation (up to 10 kGy) and ZEA (1 to 5 µg). The results revealed that independent factors had a positive significant effect on the response factor. The analysis of variance (ANOVA) was followed to fit a proper statistical model and suggested that quadratic model was appropriate. The optimized model concluded that doses of irradiation and ZEA were the determinant factors for detoxification of ZEA in fruit juices. Further, toxicological safety of irradiation mediated detoxified ZEA was assessed in the cell line model by determining the cell viability (MTT and live/dead cell assays), intracellular reactive oxygen species (ROS), mitochondrial membrane potential (MMP), nuclear damage, and caspase-3 activity. The higher level of live cells and MMP, lower extent of intracellular ROS molecules and caspase-3, and intact nuclear material were noticed in cells treated with irradiation mediated detoxified ZEA related to non-detoxified ZEA. The results confirmed that toxicity of ZEA was decreased with irradiation treatment and detoxification of ZEA by irradiation is safe. The study concluded that irradiation could be a potential post-harvest food processing technique for detoxification of ZEA mycotoxin in fruit juices. However, irradiation of fruit juices with high dose of 10 kGy has minimally altered the quality of fruit juices.